Development of Comic-Based Teaching Materials on Ocean Literacy in Elementary Schools - MUTIA YULITA SARI; M.JAYA ADI PUTRA; NENI HERMITA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2025)
The availability of contextual and engaging teaching materials is essential for improving the quality of learning, particularly in the IPAS (Natural and Social Sciences) subject. This study aims to: (1) Develop marine literacy-based comic teaching materials for fifth-grade elementary students; (2) Determine the validity and feasibility of the developed materials; and (3) Assess their effectiveness in enhancing students’ marine knowledge, behavior, and attitudes toward the sea. This research employed the Research and Development (R&D) method using the ADDIE model, which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. The limited trial subjects were fifth-grade students at SD Negeri 5 Rupat Utara, Bengkalis Regency, Riau Province. Data were collected through observation, interviews, documentation, questionnaires, and tests. The results showed that the developed comic teaching materials were highly valid (average score of 94.79%), highly feasible (teacher response 94.28% and student response 94.99%), and effective in improving student learning outcomes (N-Gain score of 0.82, categorized as high). Therefore, the marine literacy-based comic is suitable for use in IPAS learning as a medium that enhances students’ understanding and awareness of the sea from an early age.